2017
DOI: 10.3892/etm.2017.5031
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs. pulsed‑light accelerated corneal collagen cross‑linking for the treatment of progressive keratoconus: 12‑month results from a prospective study

Abstract: The aim of the present study was to compare the clinical outcomes of conventional corneal collagen cross-linking (CXL) and pulsed-light accelerated CXL (pl-ACXL) in the eyes of patients with progressive keratoconus. A total of 72 eyes with progressive keratoconus in 58 patients were equally divided into the CXL and pl-ACXL treatment groups. The CXL treatment was performed using the UVX 1000 system with 0.1% riboflavin solution in 20% dextran presoak for 30 min, and 3 mW/cm2 ultraviolet A (UVA) light for 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
6
24
0
1
Order By: Relevance
“…Jiang et al 70 documented that the DL depth in the pulsed light 30mW/cm 2 A-CXL group was 201 ± 27 µm at 1 month postoperatively confirming Mazzotta's first observation 67 as showed in Figure 4 c -d. The study revealed keratocyte apoptosis and stromal edema at 1 month postoperatively, which gradually recovered towards the normal status with no changes in the posterior stroma and endothelium. Pulsed light A-CXL 71 was safe and effective procedure in stabilizing the progression of keratoconus and by comparing the S-CXL, where the DL depth was 284.94±33.29 µm, authors obtained more effective visual and topographic outcomes than with pulsed light 30mW/cm A-CXL group.…”
Section: -Dsupporting
confidence: 54%
See 1 more Smart Citation
“…Jiang et al 70 documented that the DL depth in the pulsed light 30mW/cm 2 A-CXL group was 201 ± 27 µm at 1 month postoperatively confirming Mazzotta's first observation 67 as showed in Figure 4 c -d. The study revealed keratocyte apoptosis and stromal edema at 1 month postoperatively, which gradually recovered towards the normal status with no changes in the posterior stroma and endothelium. Pulsed light A-CXL 71 was safe and effective procedure in stabilizing the progression of keratoconus and by comparing the S-CXL, where the DL depth was 284.94±33.29 µm, authors obtained more effective visual and topographic outcomes than with pulsed light 30mW/cm A-CXL group.…”
Section: -Dsupporting
confidence: 54%
“…70,71 The pulsed light A-CXL ensured a shorter treatment time, increased the average penetration of the DL from 150 µm of the continuous light to 200 µm and reduced postoperative microstructural damage thus limiting stromal wound healing reactivity. 67,70,71 Substantially, the kinetic models after S-CXL and A-CXL protocols confirmed that there is a faster oxygen depletion and a slow oxygen replenishment shifting the CXL photodynamic reaction predominantly in the type I. It happens also in the standard protocol with continuous light UV-A exposure because of the fast oxygen consumption (10-15 sec) during the UV-ON phase.…”
Section: -Dmentioning
confidence: 99%
“…We found no significant improvement in UDVA and CDVA at 1 year following c‐ACXL and p‐ACXL. This is in keeping with a previous prospective study reporting no improvement in UDVA and CDVA at 1 year following p‐ACXL . In our series, after 24 months of follow‐up, a statistically significant improvement was noted in CDVA in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…This is in keeping with a previous prospective study reporting no improvement in UDVA and CDVA at 1 year following p-ACXL. 18 In our series, after 24 months of follow-up, a statistically significant improvement was noted in CDVA in both groups. There was no significant difference detected in mean visual acuity gain between the two groups.…”
Section: Discussionsupporting
confidence: 55%
“…The transition of crosslinked to non-crosslinked tissue is detected as a demarcation hyperreflective line within the corneal stroma ( fig.4), possibly representing the effectiveness of the CXL treatment. Studies have shown that the demarcation line is biomicroscopically detectable in slit lamp examination as early as 2 weeks after treatment and it can be equally detected by confocal microscopy and anterior segment optical coherence tomography (AS-OCT) up to a depth of aproximately 300µm [15][16][17][18].…”
mentioning
confidence: 99%